Modeling the Effects of Sensorineural Hearing Loss on Sound Localization in the Median Plane - Baumgartner, Robert (Trends Hear, 2016)
Listeners use monaural spectral cues to localize sound sources in sagittal planes (along the up-down and front-back directions). How sensorineural hearing loss affects the salience of monaural spectral cues is unclear. To simulate the effects of outer-hair-cell (OHC) dysfunction and the contribution of different auditory-nerve fiber types on localization performance, we incorporated a nonlinear model of the auditory periphery into a model of sagittal-plane sound localization for normal-hearing listeners. The localization model was first evaluated in its ability to predict the effects of spectral cue modifications for normal-hearing listeners. Then, we used it to simulate various degrees of OHC dysfunction applied to different types of auditory-nerve fibers. Predicted localization performance was hardly affected by mild OHC dysfunction but was strongly degraded in conditions involving severe and complete OHC dysfunction. These predictions resemble the usually observed degradation in localization performance induced by sensorineural hearing loss. Predicted localization performance was best when preserving fibers with medium spontaneous rates, which is particularly important in view of noise-induced hearing loss associated with degeneration of this fiber type. On average across listeners, predicted localization performance was strongly related to level discrimination sensitivity of auditory-nerve fibers, indicating an essential role of this coding property for localization accuracy in sagittal planes.